2018
DOI: 10.1029/2018jc013769
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Ice Drift Measured by Shipboard Marine Radar

Abstract: This study presents Arctic sea ice drift fields measured by shipboard marine X‐band radar (MR). The measurements are based on the maximum cross correlation between two sequential MR backscatter images separated ∼1 min in time, a method that is commonly used to estimate sea ice drift from satellite products. The advantage of MR is that images in close temporal proximity are readily available. A typical MR antenna rotation period is ∼1–2 s, whereas satellite revisit times can be on the order of days. The techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 99 publications
3
33
0
Order By: Relevance
“…The model outputs indicate that geostrophic forcing is responsible for the observed oscillations, that is, model results omitting geostrophic forcing do not reproduce the observed velocity oscillations, even for thicker ice, up to 1 m. Moreover, tidal currents have previously been found to affect ice drift only in limited water depth conditions (Mack et al, ; Meyer et al, ; Padman et al, ; Peterson et al, ), especially in shelf seas and coastal areas and, therefore, are unlikely to be the source of the periodic oscillations since the study area is located in deep waters (Arndt et al, ) where tidal currents are small. Instead, combined measurements and model outputs support the existence of a geostrophic‐like forcing at period close to 13 hr, similar to the indirect observations of Lund et al () in the Arctic. The rotational motion period and amplitude (≈2 km in diameter), similar to submesoscale eddies that have been found to form at the edge of the MIZ in the Arctic (Lund et al, ) and in numerical experiments (Dai et al, ; Manucharyan & Thompson, ), are likely driven by wind‐forced near‐inertial motion of the upper ocean in this case (Howard et al, ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The model outputs indicate that geostrophic forcing is responsible for the observed oscillations, that is, model results omitting geostrophic forcing do not reproduce the observed velocity oscillations, even for thicker ice, up to 1 m. Moreover, tidal currents have previously been found to affect ice drift only in limited water depth conditions (Mack et al, ; Meyer et al, ; Padman et al, ; Peterson et al, ), especially in shelf seas and coastal areas and, therefore, are unlikely to be the source of the periodic oscillations since the study area is located in deep waters (Arndt et al, ) where tidal currents are small. Instead, combined measurements and model outputs support the existence of a geostrophic‐like forcing at period close to 13 hr, similar to the indirect observations of Lund et al () in the Arctic. The rotational motion period and amplitude (≈2 km in diameter), similar to submesoscale eddies that have been found to form at the edge of the MIZ in the Arctic (Lund et al, ) and in numerical experiments (Dai et al, ; Manucharyan & Thompson, ), are likely driven by wind‐forced near‐inertial motion of the upper ocean in this case (Howard et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…The present data set gives a mean angle ≈−25°, as shown by the dashed line and with generally large variations from −60° to 10°. The large variations are consistent with, for example, Lund et al (), who reported turning angles from −23°to +83°during a storm event in the Arctic Basin and in other instances reported ice drift against the wind (turning angle >90°). During our measurements, the largest angles between wind and ice direction (| θ 0 |>90°) occur sporadically and are always observed for low wind speed (| u 10 |<6 m s −1 ), when the wind stresses become small.…”
Section: Drift Measurements and Analysissupporting
confidence: 90%
“…The buoys were deployed as Lagrangian floats and thus measure the wavefield in the frame of reference of the mean surface current. Although sometimes other factors influence the trajectory of a surface float, it was shown that our buoys closely follow the surface current (or sea ice) (Lund et al, 2018).…”
Section: Measurement Theory: Slope Correlationmentioning
confidence: 77%
“…We note that Pickart () mentions a mean shelf break jet with velocities of the order of 10 cm/s. However, strong mesoscale or submesoscale eddies at the ice edge have been found with velocities up to 1 m/s (Lund et al, ). Similar features have been reproduced in numerical simulations by Manucharyan and Thompson ().…”
Section: Numerical Wave Model and Resultsmentioning
confidence: 99%